Policy Options for Regulating Community Property and Community Protection Zones in Timor-Leste - World Bank (Washington, DC, 2017)
The Ministry of Justice of the Government of Timor-Leste (GoTL) has requested assistance from the World Bank Justice for the poor program to develop policy options for the implementation of chapter five of the draft land law. The present paper has been developed in response to this request. It is intended as a work in progress and a contribution to the dialogue on the community land policy of Timor- Leste. This paper sets out policy options for the implementation of chapter five of the draft land law. Based on comparative research in similar environments, and case-based research and consultations in Timor-Leste, this paper lays out the issues that the regulation implementing chapter five will most likely need to address, and for each such issue sets out several policy options available to address the issue together with analysis of the strengths and weakness of those options. The paper seeks to identify potential risks relating to the process of formulating and implementing policy for chapter five, and to describe risk mitigation strategies that have proved useful in other settings. The paper seeks to describe policy options and analyze the bases for those options, rather than recommend adoption of particular options, so as to support a detailed discussion of potential options in Timor.